Readings in public sector economics - Baker, Samuel H.; Elliot, Catherine S. (D.C. Heath, 1990)
Perspectives on economics and the public sector. Economics of externalities. Economics of public goods. Economics of the political process. Economics of taxation. Economics of fiscal federalism.